The impact on audience media brand choice using media brands uniqueness phenomenon - Linda Saulīte; Deniss Ščeulovs (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
While research on traditional media brands has increased in recent years, few studies examine news media brands and their brand strategies, particularly distinctive brand associations unrelated to media brand content and their impact on audience media brand choice and attention. Numerous studies highlight the significance of content as an element of the media brand and its vital role in audience selection. In a market where news and information are oversaturated and comparable, the dilemma for news media companies is what distinguishes them when the news content may be the same across all channels. Multi-platform consumption deludes and decreases brand associations, thus providing media brands with even more challenging brand differentiation and strong brand association management. The younger Generation Z prefers and uses more global and social media platforms than national media from the media audience perspective and future audiences. This audience consumes less national media than global and social media platforms. This is especially true of younger viewers, who are more focused on platforms and experiences. In a setting where cross-platform distribution stresses the significance of media brand associations and content experiences, the capacity of media brands to maintain brand preference and choice in a highly competitive market becomes increasingly crucial. According to the authors' analysis, data reveals that younger audiences consume less national media and prefer international media, which raises the spectrum of future domestic media audiences. Examining the unique characteristics of media brand associations that positively influence audience preference and media brand choices among younger audiences would not only answer some difficult questions for national media brands concerning how to attract younger audiences, but it would also lay the groundwork for meeting the needs of audiences for a unified media brand experience across numerous platforms, without sacrificing strong and unique media brand associations. This study focuses on national news media brands and analyses the attributes of news media brands, as well as their significance for the Generation Z audience in media brand choice and engagement. The study highlights the importance of content experience in defining the uniqueness of media brands and its effect on brand selection and audience consumption. The authors used linear regression analyses and the decision tree approach to predict the most significant correlations between media brand attributes and brand uniqueness.
Keywords: 650; media brand attributes; media brand uniqueness; news media brand